Cerebellar degeneration in primary lateral sclerosis: an under-recognized facet of PLS. Issue 7 (2nd October 2022) - Finegan, Eoin; Siah, We Fong; Li Hi Shing, Stacey; Chipika, Rangariroyashe H.; Hardiman, Orla; Bede, Peter
Abstract: While primary lateral sclerosis (PLS) has traditionally been regarded as a pure upper motor neuron disorder, recent clinical, neuroimaging and postmortem studies have confirmed significant extra-motor involvement. Sporadic reports have indicated that in addition to the motor cortex and corticospinal tracts, the cerebellum may also be affected in PLS. Cerebellar manifestations are difficult to ascertain in PLS as the clinical picture is dominated by widespread upper motor neuron signs. The likely contribution of cerebellar dysfunction to gait disturbance, falls, pseudobulbar affect and dysarthria may be overlooked in the context of progressive spasticity. The objective of this study is the comprehensive characterization of cerebellar gray and white matter degeneration in PLS using multiparametric quantitative neuroimaging methods to systematically evaluate each cerebellar lobule and peduncle. Forty-two patients with PLS and 117 demographically-matched healthy controls were enrolled in a prospective MRI study. Complementary volumetric and voxelwise analyses revealed focal cerebellar alterations instead of global cerebellar atrophy. Bilateral gray matter volume reductions were observed in lobules III, IV and VIIb. Significant diffusivity alterations within the superior cerebellar peduncle indicate disruption of the main cerebellar outflow tracts. These findings suggest that the considerable intra-cerebellar disease-burden is coupled with concomitant cerebro-cerebellar connectivity disruptions. While cerebellar dysfunction is challenging to demonstrate clinically, cerebellar pathology is likely to be a significant contributor to disability in PLS.